2015
DOI: 10.1002/jor.22848
|View full text |Cite
|
Sign up to set email alerts
|

A bioreactor system for in vitro tendon differentiation and tendon tissue engineering

Abstract: There is significant clinical demand for functional tendon grafts in human and veterinary medicine. Tissue engineering techniques combining cells, scaffolds and environmental stimuli may circumvent the shortcomings of traditional transplantation processes. In this study, the influence of cyclic mechanical stimulation on graft maturation and cellular phenotype was assessed in an equine model. Decellularized tendon scaffolds from four equine sources were seeded with syngeneic bone marrow-derived mesenchymal stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 45 publications
3
76
2
Order By: Relevance
“…Here, mechanical stimulation was performed over 8 or 10 days until samples were harvested; hence, the results of the present study add to these published data very well. Youngstrom et al found increased gene expression levels of scleraxis, collagen 1, and decorin but decreased expression of collagen 3 when using a stimulation regime with 3% strain, being accompanied by improved biomechanical properties [39]. Considering Youngstrom et al's and our findings at the same time, it can be assumed that scleraxis and decorin expression levels not only are elevated very early but can be maintained in the model system used.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Here, mechanical stimulation was performed over 8 or 10 days until samples were harvested; hence, the results of the present study add to these published data very well. Youngstrom et al found increased gene expression levels of scleraxis, collagen 1, and decorin but decreased expression of collagen 3 when using a stimulation regime with 3% strain, being accompanied by improved biomechanical properties [39]. Considering Youngstrom et al's and our findings at the same time, it can be assumed that scleraxis and decorin expression levels not only are elevated very early but can be maintained in the model system used.…”
Section: Discussionsupporting
confidence: 70%
“…Intriguingly, studies using an approach very similar to the current one, combining cell culture on decellularized tendon scaffolds and mechanical stimulation, were published recently [39, 43]. Here, mechanical stimulation was performed over 8 or 10 days until samples were harvested; hence, the results of the present study add to these published data very well.…”
Section: Discussionmentioning
confidence: 56%
“…When canine ASCs were grown in 3D culture in a collagen and human tendon ECM composite hydrogel with static tension, the cells underwent differentiation towards tenocytes and showed increased alignment and tenomodulin expression [44]. One group observed improved horse MSC integration and differentiation into thick horse tendon ECM sections with 3% strain compared to lesser values [26]. To increase tendon-like architecture of the material, one study took canine MSC-seeded tendon sections and sutured them together to create bundles that were cultured in suspension.…”
Section: Ecm Effects On Cell Differentiationmentioning
confidence: 99%
“…The bioreactor was first operated without phonatory stimulation for a duration of 3 days. 9,15,27,28 Subsequently, the bioreactor was phonated for 2 h each day over a period of 4 days. The bioreactor was phonated for 1 h, rested for 15 min, and phonated for another hour.…”
Section: Phonatory Stimulationmentioning
confidence: 99%